(3GdeHGMK GdLdjdI aj JMQjQ ebGUO GdhSjdIs - (3YHO GdbGOQ Hf eMeO Hf SGde GdeLdSjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd GdYHO YHO GdbGOQ Hf eMeO Hf eMeO SGde GdeLdSi CeG HYO aEf GdEYJfGA HGdYde ef CSfi GdbQHGJ hgh CSei eG CfabJ ajg faGFS GdChbGJ s
(3BNQgG (B:s
(3hai GdTaGA EYde Cf Gddg Ld ESeg bGOQ Ydi Ndb GdeYQaI ai bhdH YHGOg GdeDefjf hGdYde HPGJg hCSeGFg hUaGJg hLejY JcdjaGJg GHJOGA hOhf hGSWI dhTGA ceG Mci Yf SfJg ai HYV GdCfHjGA s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eYfhfI HGdMHQ GdCMeQ s
(3hYdjgG hbajGJ hJUMjMGJ HMhGTjgG s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJhMjO hGdedd hGdfMds